Isolation, Identification and Analysis of Probiotic Properties of Lactic Acid Bacteria from Selective Various Traditional Thai Fermented Food and Kefir - Powthong, Pannapa; Suntornthiticharoen, Pattra (Pakistan Journal of Nutrition, 2015)
A total of 499 lactic acid bacteria were isolated from 93 samples traditional Thai fermented food (91 samples) and kefir (2 samples). Antimicrobial activities of all isolates grown under oxygen-restricted conditions to eliminate the effect of hydrogen peroxide were tested against 20 intestinal and urogenital pathogenic bacterial using directed agar and spot on lawn technique. Thirty one isolates exhibited antimicrobial activity against at least one indicator strain tested. We observed that Shigella boydii and Shigella flexneri were the most inhibited pathogen. The characterization of the microorganism as probiotic were tested by growth in wide temperature ranges (25-45°C), salt, bile salt and acid tolerant, antibiotic sensitivity, cell surface hydrophobicity, hemolysis pattern and cell free agar diffusion method. Results showed that there were 4 isolates which showed effective antimicrobial activities and probiotic properties. Diversity of lactic acid bacteria with antimicrobial activities was studied by identification to the species level of the 4 isolates by using API 50 CHL test kit. Of the 4 isolates, 2 isolates were identified as Lactobacillus plantarum, the other 2 isolates were identified as Lactobacillus pentosus (1 isolates) and Lactobacillus brevis (1 isolate). Therefore, these strains may have potential use as an alternative to antibiotics. The strains can also be used to produce antimicrobial compounds which can be a substitute for chemical preservatives in food industry.